Down a dark road [compact disc, unabridged] - Castillo, Linda (Castillo, Linda. Kate Burkholder novel., 2017)
When a kidnapper releases Kate Burkholder unharmed, asking her to prove his innocence, Kate begins to wonder whether the police are hiding something, and she embarks on her own investigation to discover the truth.